IMMUNORESISTATION OF EXPERIMENTAL ANIMALS OF DIFFERENT AGE IN SIMULATED GENERALIZED INFLAMMATORY PROCESS - Коваленко Т. І.; Мінухін В. В.; Клімова О. М. (World of Medicine and Biology, 2015)
The paper presented that young animals are more responsive to the introduction of the bacterial suspension P.aeruginosa and old experimental animals to the introduction of a suspension of E. coli. The primary humoral immune response factor was reduced in young experimental animals. Just come to the conclusion that outcome of inflammation in experimental animals depends on the age characteristics, the functional state of the factors of innate immunity, against bacteria of different types of accessories and the stage of the inflammatory process.